Elena Fortún and the Residencia de Señoritas Librarianship Group (1930-1936) - Melián Pérez, Elvira María (Historia y Memoria de la Educación, 2018)
The librarianship studies, developed under the auspices of the Boston International Institute by the «Residencia de Señoritas» between 1930 and 1936, were part of the first educational initiatives taken to promote the integration of women into the labour force of Spain. These studies were led by Maria de Maeztu. Along with significant figures like Elena Fortún, a huge collective of anonymous students participated and deposited in this enterprise their important personal prospects. In this work we have investigated the information included in their registration forms as well as Elena Fortún’s testimony regarding this activity. We have attempted to recover the human spirit or, in other words, the inside history of this pioneering effort, truncated by the Spanish Civil War and its final outcome.